Occupational radiation dose to persons involved in veterinary positron emission tomography - Martinez, Nicole, author; Johnson, Thomas, advisor; Kraft, Susan, committee member; Ryan, Stewart, committee member (Colorado State University. Libraries, 2011)
Several studies have been conducted concerning the dose to hospital personnel from positron emission tomography (PET) radiopharmaceuticals, but to date no specific parallel studies have been done for veterinary PET technologists. Compared to human PET imaging, veterinary personnel are potentially interacting with animal patients for a longer time period, sometimes in close physical proximity, because of the need for anesthetizing patients. There is no equivalent data on personnel exposure from human PET imaging; human patients are not anesthetized and are kept in an isolated room after injection until their imaging procedure. Although veterinary personnel may be interacting more closely with animal patients undergoing PET imaging, radiopharmaceutical doses are generally smaller for animal patients because they weigh less on average. Considering these and other differences between human and veterinary practice, this study aimed to determine, on a per patient basis, the dose to personnel working with PET at Colorado State University's (CSU) James L. Voss Veterinary Teaching Hospital (VTH). Electronic personal dosimeters (EPDs) and supplemental optically stimulated luminescence (OSL) dosimeters were used (in addition to regular dosimetry) to determine radiation doses to veterinary personnel over a period of four months. Participants in the study included nuclear medicine technologists, the on-duty anesthesiology technologist, and occasionally an observer. Individual doses, along with the details of the staff member's activities, were recorded for available personnel for each PET study. Twenty-five scans were conducted over the course of this study: thirteen different dogs, six different cats, and a sheep (with two cats and three dogs having repeat scans). The mass range of the animals was 2.8 to 76.5 kg, with an average of 28.9 kg. The average amount of activity injected was 6 MBq per kg. The dose range for the nuclear medicine technologists was 0 to 30 μSv (7.8 μSv average), for the anesthetist 1 to 22 μSv (8.3 μSv average), and for the observer 0 to 2 μSv (0.4 μSv average).
Keywords: health physics; veterinary medicine; positron emission tomography; occupational radiation safety